Skipping breakfast is associated to inadequate nutrient intakes among Tunisian children: a cross-sectional study - El Ati, Jalila; Doggui, Radhouene; Dogui, Darine; El Ati-Hellal, Myriam (Frontiers in Pediatrics, 2024)
Breakfast is widely acknowledged as a crucial meal of the day, particularly for children, owing to its role in supplying essential nutrients and energy necessary for optimal growth and cognitive function. This study aims to examine differences in nutrient intake between breakfast skippers and non-skippers among children. A representative sample of 1200 Tunisian preschool and schoolchildren, aged 3-9 years, was randomly selected from kindergartens and primary schools in the Greater Tunis region which includes four governorates (Tunis, Ariana, Manouba and Ben Arous) using a two-stage cross-sectional design. Stratification was carried out depending on each of the selected governorates and urban/rural areas. Dietary intake was evaluated using the 24-hour recall method and a diet history covering the week preceding the survey. Nutritional food composition was derived from a specific Tunisian food composition database. Nutrient intake below age-and sex-specific reference values was considered inadequate. The findings indicate that the daily intake of energy and nutrients was lower among breakfast skippers compared to regular breakfast eaters. After adjusting for energy, gender, age, bmi and household economic proxy, the daily consumption of total sugar, riboflavin, vitamin B-5, phosphorus and calcium was higher among breakfast consumers while saturated fatty acid intake was higher among skippers.A comparative analysis of daily mean food category intake between the two groups revealed a higher consumption of milk and dairy products among breakfast consumers. Regular breakfast consumption is an important part of maintaining a balanced diet and healthy weight.